Rachel - Sahl, Ted (photographer):::Creator::::::::::::
Photograph shows female impersonator Raymond P. Aguilar dressed as Rachel at Desperados. She is wearing a feathered headdress, leopard print outfit, fur trimmed cape, and high heels.